SPK Penilaian Hasil Belajar Siswa Dengan Metode TOPSIS - Anita Sindar RM Sinaga (Universitas Mercu Buana, 2020)
In the learning process students get an assessment. The teacher plays the role of accumulating student values from each assignment given. The results of the assessment are often less objective and not transparent. Measurement of the process and learning outcomes in the form of numbers that reflect the achievements, processes and learning outcomes. A technology-based assessment system is needed that supports making decisions determining student grades. The things that affect student learning assessment are categorized as assessment criteria. Each criterion is given a weight (%). The decision system that supports the assessment in this study uses the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method, the weights of each criterion value form the matrix, normalized to obtain the highest assessment score. Ranking stages are obtained from the results of alternative matrices and criteria weights. The application of the Topsis method for Assessment of Student Learning Outcomes at SMK Negeri 1 Pantai Labu with the provisions of the criteria and weight data obtained by a student named Trisna Supiyati obtained the highest rating.